THE EFFECT OF MENTAWAI BEACH SAND AS A SUBSTITUTE FOR RIVER SAND ON THE COMPRESSIVE STRENGTH OF CONCRETE - A, Arman.; Mulyati, Mulyati; Fajar, Fajar; Roza, Angelalia; Marizal, Yoharis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The Concrete technology innovation is always required to answer the challenges of the need for the resulting concrete to be of high quality including strength and durability without ignoring economic value. One of the additional materials can be using pumice for fine aggregate. In such conditions, it is possible that the need for quality fine aggregates will be difficult to fulfill. The aim of this research is to determine the effect of variations in the use of sea sand on the compressive strength of concrete. This research is experimental in nature and was carried out in the Civil Engineering laboratory of the Padang Institute of Technology (ITP). Standard regulations for concrete mixing specifications use SNI 7656-2012 which concerns